Strings, Bears, & Boards: Making Fractions Meaning-filled (pp. 54–60) - Druken, Bridget K; Marzocchi, Alison S (Ohio Journal of School Mathematics, 2019)
To successfully operate with fractions, decimals and percents, it is imperative to first provide pre-service teachers the opportunity for making sense of the meaning of fractions. The Common Core State Standards and associated Progressions document provide guidelines for building fraction understanding. In this article, the authors present a series of fraction meaning activities designed for pre-service teachers that have been implemented and improved through ten iterations of lesson study. The activities use physical models that link pre-service elementary teachers’ fraction reasoning to Common Core Standards. Using string, counting bears, and geoboards, these meaningful fraction activities show how a copies of 1/b of some whole, or a/b, can be seen in linear, discrete, and area contexts.